GAMBARAN HISTOPATOLOGI LAMBUNG TIKUS WISTAR (Rattus norvegicus) YANG DIBERIKAN VITAMIN C (Asam askorbat) DOSIS TINGGI - Baharuddin, Juwita P. S. (Universitas Sam Ratulangi, 2013)
Abstract: Background: Vitamin C is one of the chemicals which are acidic and therefore is able to irritate the stomach lining if consumed in excessive amount. Objective: To reveal the histopathological features of the stomach of wistar rats supplemented with high doses of vitamin C. Method: Experimental study employing eight wistar rats divided into three groups. Rats in group A were fed with regular pellets for 12 days. Rats in group B were fed with regular pellets and were supplemented with vitamin C at 6 mg/day for 12 days. Rats in group C were fed with regular pellets and were supplemented with vitamin C at 8 mg/day for 12 day. Results: Rats in group A showed normal stomach features. Rats in group B revealed PMN inflammatory cells and hiperemy on the mucosal lining, submucosa, and muscularis mucosae. Moreover, edema on the mucosal lining was also seen in the rats in this group. Similar histopathological features were also demonstrated by the rats in group C. In this group the number of PMNs and hiperemy was greater than that of group B; in addition, cell regeneration was also seen in this group. Conclusion: Supplementation of high doses of vitamin C at 6 mg/kg and 8 mg/kg of body weight per day for 12 days may lead to changes in histopathological features of the stomach of wistar rats. Keywords: acute gastritis, vitamin C. Abstrak: Latar Belakang: vitamin C merupakan salah satu bahan kimia yang bersifat asam, sehingga apabila dikonsumsi berlebihan dapat mengiritasi lambung. Tujuan: Untuk mengetahui gambaran histopatologi lambung tikus wistar yang diberikan vitamin C dosis tinggi. Metode: Penelitian eksperimental dengan 8 ekor tikus wistar dibagi menjadi 3 kelompok. Kelompok A diberikan pelet biasa selama 12 hari. Kelompok B diberikan pelet biasa dan vitamin C 6 mg/hari selama 12 hari. Kelompok C diberikan pelet biasa dan vitamin C 8 mg/hari selama 12 hari. Hasil: Pada kelompok A didapatkan gambaran lambung yang normal. Kelompok B terlihat sel-sel radang PMN dan hiperemi pada lapisan mukosa, sub mukosa dan muskularis, pada kelompok ini juga terlihat edema pada lapisan mukosa. Kelompok C terlihat pada lapisan mukosa, submukosa dan muskularis adanya sel-sel radang PMN dan hiperemi yang lebih banyak dibandingkan kelompok B, selain itu juga terlihat regenerasi sel. Kesimpulan: Pemberian vitamin C dosis tinggi yaitu 6 mg/hari dan 8 mg/hari selama 12 hari dapat mengakibatkan perubahan gambaran histopatologi lambung. Kata Kunci: Gastritis akut, vitamin C.